Assessment of the size of the Khmelnytskyi NPP observation zone taking into account power units No. 5 and 6 with the AP1000 reactor - М. М. Тalerko; Т. D. Lev; А. V. Nosovskyi; V. М. Rudko; А. М. Novikov; O. V. Blokhina (Ядерна фізика та енергетика)
An assessment of the size of the observation zone (OZ) of the Khmelnytskyi NPP was carried out, taking into account the potential impact of power units No. 3 and 4 with the VVER-1000 reactor and No. 5 and 6 with the AP1000 reactor manufactured by the Westinghouse Electric Company. The calculations were carried out based on the requirements of the document NP 306.2.173-2011 "Requirements for determining the dimensions and boundaries of the observation zone of a nuclear power plant". When calculating the radiation doses to the population in the initial period of the radiation accident, contributions from the inhalation of radionuclides into the human body and external radiation from the cloud and fallout on the soil surface were taken into account. The size of the observation zone of the Khmelnytskyi NPP was determined based on not exceeding the criteria for the introduction of urgent countermeasures (lower limits of justification) in the event of a beyond-basis design accident at one of the power units. The determining factor for determining the OZ size is not exceeding the criterion for the effective radiation dose for the critical age group "1 year" in the event of an accident at power units with VVER-1000 reactors. The main way of forming an effective dose of radiation is external exposure from depositions on the ground. (93 % for 1-year-old children and 94 % for adults). The main part of the effective dose for the critical age group "1 year" is formed due to the contribution of 131-135I in aerosol and organic forms, which is almost 89 %. The share of long- and medium-lived radionuclides in the form of aerosols is about 7.3 %, of which 6.9 % is the contribution of cesium isotopes. The contribution of inert radioactive gases is about 4 %. The size of the observation zone of the Khmelnytskyi NPP, calculated on the condition that all six power units are put into operation, is obtained to be 13.600 m. A conclusion was made that re-establishment of the dimensions of the observation zone of the Khmelnytskyi NPP is not advisable after the commissioning of the new units No. 3 and 4 with VVER-1000 reactors and No. 5 and 6 units with AR1000 reactors.